Silicon Mode (de)Multiplexer Based on Cascaded Particle-Swarm-Optimized Counter-Tapered Couplers - Weiwei Chen; Hongxiang Li; Bohao Zhang; Pengjun Wang; Shixun Dai; Yuxiao Liu; Jun Li; Yan Li; Qiang Fu; Tingge Dai; Hui Yu; Jianyi Yang (IEEE Photonics Journal)
In this paper, a design of a silicon mode (de)multiplexer based on cascaded counter-tapered couplers is proposed and investigated. By using the particle swarm optimization algorithm and finite difference time domain method, structural parameters of each counter-tapered coupler in our proposed mode (de)multiplexer are optimized so that high conversion efficiencies can be obtained and coupling lengths can be significantly shortened. The coupling lengths of counter-tapered couplers in the proposed silicon four-mode (de)multiplexer operating in transverse-electric polarization are 8 μm, 9 μm, and 10 μm. The corresponding conversion efficiencies are respectively 98.98%, 99.98%, and 98.68%. Experimental results show that, the fabricated device exhibits a demultiplexed crosstalk of −32.76 dB, −27.10 dB, −32.45 dB, or −33.29 dB at 1550 nm wavelength, when the fundamental transverse-electric mode is respectively launched into the ports Input0, Input1, Input2, or Input3. The measured demultiplexed crosstalk is less than −15.15 dB from 1525 to 1596 nm and lower than −18.12 dB from 1525 to 1561 nm.